Beyond nutrition: modification of the carotenoid profile as a potential strategy to regulate tomato fruit ripening and shelf-life - Orsi, Bruna (2023)
Carotenoids are important pigments in defining the aroma, flavor, appearance, and nutritional properties of fruits. In addition, they are also involved in the synthesis of regulators of plant development, such as abscisic acid (ABA). We previously observed that fruits from different carotenoid profile display altered ethylene (ETH) production. Recent reports suggest a link between carotenoid-synthetizing enzymes and the regulation of ripening, as their genetic manipulation alters ABA production and, in turn, ETH levels during late ripening. Despite these reports, the genetic manipulation of the carotenoid profile by the industry often aims at improved nutritional properties of fruits, and much is still to be explored about an additional role of carotenoids as components of the hormonal cascade that regulates ripening. Here, we gathered physiological data on the postharvest ripening of Micro Tom near-isogenic lines carrying alleles that alter the accumulation of carotenoids and showed that the ripening progress may be affected by the pigment profile. Two carotenoid mutants, one with impaired activity of Phytoene-synthase (PSY1), and another with gain-of-function of Lycopene-β-cyclase were confronted with the ABA-deficient mutant sitiens and the ripening mutant ripening inhibitor. From this approach, we observed that spontaneous carotenoid mutations alter the ABA and ETH crosstalk and with that, the advancement of ripening. Results were detailed throughout three chapters where we discuss (i) a possible involvement of PSY1 in the autocatalytic feedback loop that regulates ETH synthesis; (ii) the impact of the carotenoid profile in the ABA-ETH network and fruit quality, and (iii) the different outcomes on maturity parameters when fruits ripens attached to the plant or in postharvest storage. Together, our findings suggest that the manipulation of the carotenoid profile may be a strategic tool for postharvest storage, aiming at fruits with improved nutrition properties and additionally, with extended shelf life.